Public Service Motivation Measurement: A Test of Perry's Scale in Indonesia - Hety Budiyanti; shine pintor siolemba patiro; akhmat yamin (Magister Administrasi Publik, 2019)
This article proposes and tests a ‘shorter version of the instrument for public service motivation based on Perry’s (1996) exploratory 24-item scale for Indonesia civil servants in five big cities, inter alia, Jakarta, Surabaya, Semarang, Makassar, and Medan. Of 1200 respondents, 904 completed the questionnaire, and 800 questionnaires were determined to be feasible for further analysis. Thus, the response rate was 88.50% the results indicated support for the shortened scale of Perry’s original work on investigating the Public Service Motivation (PSM) of Indonesia civil servants in sample cities. The 10-item scale was based on four factors PSM, inter alia Attraction to Policy Making (APM), Commitment to the Public Interest (CPI), Compassion (COM), Self-Sacrifice (SS). Results also showed that, generally PSM for civil servant with basic positions in city government offices, in five cities tends to vary. The research results are expected to enhance our understanding about the importance of factors that influence the motivation of civil servants in providing public services to the general public. However, the limitation of the study lies in the small sample which is drawn from only five large cities in Indonesia.